Modeling Interoperable Information Systems with 3LGM(2) and IHE. - Staubert, S.; Schaaf, M.; Jahn, F.; Brandner, R.; Winter, A. (Methods Inf Med, 2015)
BACKGROUND: Strategic planning of information systems (IS) in healthcare requires descriptions of the current and the future IS state. Enterprise architecture planning (EAP) tools like the 3LGM(2) tool help to build up and to analyze IS models. A model of the planned architecture can be derived from an analysis of current state IS models. Building an interoperable IS, i. e. an IS consisting of interoperable components, can be considered a relevant strategic information management goal for many IS in healthcare. Integrating the healthcare enterprise (IHE) is an initiative which targets interoperability by using established standards. OBJECTIVES: To link IHE concepts to 3LGM(2) concepts within the 3LGM(2) tool. To describe how an information manager can be supported in handling the complex IHE world and planning interoperable IS using 3LGM(2) models. To describe how developers or maintainers of IHE profiles can be supported by the representation of IHE concepts in 3LGM(2). METHODS: Conceptualization and concept mapping methods are used to assign IHE concepts such as domains, integration profiles actors and transactions to the concepts of the three-layer graph-based meta-model (3LGM(2)). RESULTS: IHE concepts were successfully linked to 3LGM(2) concepts. An IHE-master-model, i. e. an abstract model for IHE concepts, was modeled with the help of 3LGM(2) tool. Two IHE domains were modeled in detail (ITI, QRPH). We describe two use cases for the representation of IHE concepts and IHE domains as 3LGM(2) models. Information managers can use the IHE-master-model as reference model for modeling interoperable IS based on IHE profiles during EAP activities. IHE developers are supported in analyzing consistency of IHE concepts with the help of the IHE-master-model and functions of the 3LGM(2) tool CONCLUSION: The complex relations between IHE concepts can be modeled by using the EAP method 3LGM(2). 3LGM(2) tool offers visualization and analysis features which are now available for the IHE-master-model. Thus information managers and IHE developers can use or develop IHE profiles systematically. In order to improve the usability and handling of the IHE-master-model and its usage as a reference model, some further refinements have to be done. Evaluating the use of the IHE-master-model by information managers and IHE developers is subject to further research.
Keywords: *Computer Graphics; Electronic Health Records/*organization & administration; Guidelines as Topic; Health Information Systems/*organization & administration; Internationality; Medical Record Linkage/*standards; *Models, Organizational; Models, Theoretical; Systems Integration